EXAMINING THE EFFECT OF INFORMATION QUALITY AND INFORMATION ADOPTION ON PURCHASE INTENTION TOWARDS LOCAL COSMETIC PRODUCTS AMONG YOUNG CONSUMERS IN SABAH - Rosly, Ameera Raihanah; Ahmad, Siti Nor Bayaah (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2025)
The study examines the effects of information quality and information adoption on purchase intention towards local cosmetic products among young consumers in Sabah, with a specific focus on the mediating role of information adoption. The research framework is based on the Information Adoption Model (IAM), which explains how individuals process and accept information, influencing their purchasing behavior. A quantitative research approach was employed, utilizing a questionnaire to collect data from 170 respondents. The data were analyzed using SmartPLS, a software for partial least squares structural equation modeling (PLS-SEM). The findings reveal that information quality (β = 0.196, p < 0.05), information usefulness (β = 0.369, p < 0.001), and information credibility (β = 0.444, p < 0.001) significantly and positively influence information adoption. Furthermore, information adoption exhibits a strong positive effect on purchase intention (β = 0.778, p < 0.001), explaining 60.3% of its variance. The study also confirms the mediating role of information adoption in the relationships between information quality (β = 0.153, p < 0.05), usefulness (β = 0.287, p < 0.001), credibility (β = 0.345, p < 0.001), and purchase intention, highlighting its pivotal role in consumer decision-making. The research underscores the importance of high-quality, credible, and useful information in shaping young consumers’ attitudes toward local cosmetic brands. Social media platforms, particularly Instagram and TikTok, emerge as critical channels for disseminating such information, with online reviews and influencer endorsements significantly impacting purchase intentions. Theoretical contributions include an extension of the IAM in the context of local cosmetics, addressing a gap in literature regarding young consumers in Sabah. Managerially, the study advocates for targeted marketing initiatives, leveraging influencer partnerships and educational content to improve information adoption and drive sales. Future research could expand demographic diversity, employ longitudinal designs, and explore cross-cultural comparisons to further validate these findings.